Comparison of HRCT of chest findings in different waves during the COVID-19 pandemic: a retrospective descriptive study in COVID dedicated hospital in Bangladesh - Kamal, S. M. Sorowar; Borhanuddin, M.; Fatema, Kaniz; Shams, Fahmida; Akter, Sheikh Rabeya; Rahman, Mohammad Ahmadur (International Journal of Research in Medical Sciences, 2023)
Background: The existing COVID-19 epidemic has affected masses of people universally, leading to significant morbidity and mortality. Radiological imaging methods such as high-resolution computed tomography (HRCT), computed tomography (CT) and chest x-ray have played an essential role in diagnosing and managing COVID-19. Methods: This cross-sectional and observational study was conducted in the department of radiology and imaging, Kurmitola General Hospital, Dhaka, Bangladesh, a COVID dedicated hospital. A total number of 469 patients (N=469) from ≤20 to ≥90 years old were included in the study. Data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 25.0. Results: Based on distribution by age group, the highest number of cases in all three waves were among individuals aged 51-60 (126, 26.9%), followed by those aged 61-70 (97, 20.7%) and 41-50 (90, 19.2%). Among the patients with subtle GGO, the proportion of cases was highest in the first wave, followed by a decrease in the second wave and a further decrease in the third wave. The proportion of patients with SCL was highest in the second (44.9%) wave and decreased in the third (5.9%) wave. For both LUL and LLL, the majority of cases with radiological were observed in the “yes” group in all waves, with significantly higher proportions in the “yes” group compared to the “no” group (p value <0.001). Conclusions: The findings highlighted the significance of incorporating routine radiological examinations and monitoring of radiological features in managing and treating COVID-19 patients. The findings in the study also suggested that the percentage of lung involvement increased from the first to the third wave of COVID-19, which is consistent with the increasing trend of COVID-19 cases during the same period.